Banking sector reforms is China following Japan's footstep? - Hassan, M. Kabir 1963-; Dulal Miah, Md (Cambridge elements, 2022)
China registered double-digit GDP growth for more than three decades. Recently, the rate has slowed down considerably. The slow growth period, which Chinese policymakers refer to as the 'new-normal', has created enormous curiosity among scholars and policymakers. In particular, scholars often tend to project if China is destined to follow Japan's fate. Insufficient reforms in the banking sector in commensuration with the real economy in Japan resulted in an unprecedented financial catastrophe. Similarly, an asymmetric development between the Chinese banking sector and the real economy is observed. This leads to an interesting question: is China destined to meet Japan's legacy? This Element attempts to answer this question. In so doing, it delves deep into the banking sector reforms of China. The Element concludes that China is not on course to meet an immediate financial chaos, but the country needs further banking reforms to avoid a potential crisis